Tinjauan Kritis terhadap Desain dan Validitas Temuan dalam Penelitian Penerapan Strategi Circuit Learning pada Pembelajaran Matematika Sekolah Dasar - Yolinus Wenda; Azril Irzam (CV. Global Cendekia Inti, 2026)
This article presents a critical review of research design and the validity of findings in studies on the application of Circuit Learning strategies in primary school mathematics education. The main focus is on evaluating the predominant use of the one-group pretest–posttest design in previous research and its implications for internal validity, external validity, and the reliability of measurement instruments. The analysis indicates that although prior studies report significant improvements in students’ mean learning outcomes and gain scores, the research designs employed are limited in their ability to establish strong causal relationships. Threats to internal validity—such as maturation effects, historical influences, and instrumentation bias—as well as issues of limited generalisability, emerge as key concerns. This article emphasises that while Circuit Learning demonstrates potential for enhancing student engagement and mathematical understanding, claims of its effectiveness should be regarded as indicative until tested through more rigorous research designs, such as quasi-experimental studies with control groups. The conclusions of this review provide direction for future research to strengthen methodological validity, improve instrument reliability, and optimise the implementation of Circuit Learning in primary education.